Children’s literature and tenderness: Pedagogical reflections on the gestures of care, the well-being of relationships and affection in picture books - Marcella Terrusi (Encyclopaideia)
The contribution offers some pedagogical reflections dedicated to the theme of tenderness in education through the exploration of a repertoire of excellent picture books published in the field of children’s publishing. The poetic investigation of the suggestions from the bibliographic corpus highlights ethical, aesthetic and pedagogical aspects of bodily imagery and experiences, linked to the sensitive, ethical and emotional dimension of education. The reflection interweaves perspectives from the pedagogy of the body with the interdisciplinary study of children’s literature and proposes a pedagogical reflection, with didactic and formative repercussions, on the iconographic and narrative representations of the postures of care, play and the educational relationship.